TRAWL FISHERIES OF THE SOUTH KANARA COAST DURING 1967-70 - Ramamurthy, S (Indian Journal of Fisheries, 2011)
The trawl catch and the catch rate showed great fluctuations during Jhedifferent years at Mangalore. Best catches were generally during February-May.Prawns constituted the single largest group, followed by flat fishes, silver-bellies,and sciaenids. High catch rates for prawns and fish were observed in thesouthern and northern parts of this coast respectively. The catch rate for all fishshowed a decline during 1969-70 throughout the entire coast, that at Malpe,being exceptionally low, despite a four-fold increase in fishing effori there.